2008
DOI: 10.1179/102453308x315933
|View full text |Cite
|
Sign up to set email alerts
|

Leukemic infiltration of the breast in acute lymphocytic leukemia (ALL)

Abstract: Extramedullary leukemic infiltration of the breast in adult acute lymphocytic leukemia (ALL) is rare. We report two such cases here. One patient died of relapsed ALL and the other was cured with local radiation therapy and remains alive and in remission 30 years after relapsing in her breast. A literature review of reported cases of ALL with breast involvement is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The mechanism of extramedullary infiltration is unclear. In studies of extramedullary AML, the expression of adhesion molecules such as CD56 was associated with extramedullary granulocytic sarcoma, which occurred in 3% to 7% of AML cases [56]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of extramedullary infiltration is unclear. In studies of extramedullary AML, the expression of adhesion molecules such as CD56 was associated with extramedullary granulocytic sarcoma, which occurred in 3% to 7% of AML cases [56]. …”
Section: Discussionmentioning
confidence: 99%
“…The median age in those patients was16 years [3]. Four cases with similar presentation of adultALL have been published (Table 1) [4,5,6,7]. Sagar et alreported a similar occurrence in a 35-year-old female, butdetails on immunophenotyping, response, remission status,and outcome were not available [4].…”
Section: To the Editormentioning
confidence: 99%
“…Chim et al reported asimilar case in a 23-year-old male with previous diagnosis ofT-cell ALL who died of progressive disease after 7 months ofrelapse [5]. Two other cases with similar presentation havebeen reported [6,7]. All patients reported with adult ALLwere between the ages of 23 and 35 years.…”
Section: To the Editormentioning
confidence: 99%
“…[1] Patients with lymphoblastic or leukemic infiltration of the breast usually present with a palpable lesion that is generally well circumscribed and rapidly enlarging. The lesion may be bilateral and/or multifocal simulating a fibroadenoma.…”
Section: Introductionmentioning
confidence: 99%